Treatment outcomes of adult patients with recurrent tuberculosis in relation to HIV status in Zimbabwe: a retrospective record review - Takarinda Kudakwashe C; Harries Anthony D; Srinath Satyanarayana; Mutasa-Apollo Tsitsi; Sandy Charles; Mugurungi Owen (BMC, 2012)
Abstract Background Zimbabwe is a Southern African country with a high HIV-TB burden and is ranked 19th among the 22 Tuberculosis high burden countries worldwide. Recurrent TB is an important problem for TB control, yet there is limited information about treatment outcomes in relation to HIV status. This study was therefore conducted in Chitungwiza, a high density dormitory town outside the capital city, to determine in adults registered with recurrent TB how treatment outcomes were affected by type of recurrence and HIV status. Methods Data were abstracted from the Chitungwiza district TB register for all 225 adult TB patients who had previously been on anti-TB treatment and who were registered as recurrent TB from January to December 2009. The Chi-square and Fischer's exact tests were used to establish associations between categorical variables. Multivariate relative risks for associations between the various TB treatment outcomes and HIV status, type of recurrent TB, sex and age were calculated using Poisson regression with robust error variance. Results Of 225 registered TB patients with recurrent TB, 159 (71%) were HIV tested, 135 (85%) were HIV-positive and 20 (15%) were known to be on antiretroviral treatment (ART). More females were HIV-tested (75/90, 83%) compared with males (84/135, 62%). There were 103 (46%) with relapse TB, 32 (14%) with treatment after default, and 90 (40%) with "retreatment other" TB. There was one failure patient. HIV-testing and HIV-positivity were similar between patients with different types of TB. Overall, treatment success was 73% with transfer-outs at 14% being the most common adverse outcome. TB treatment outcomes did not differ by HIV status. However those with relapse TB had better treatment success compared to "retreatment other" TB patients, (adjusted RR 0.81; 95% CI 0.68 - 0.97, p = 0.02). Conclusions No differences in treatment outcomes by HIV status were established in patients with recurrent TB. Important lessons from this study include increasing HIV testing uptake, a better understanding of what constitutes "retreatment other" TB, improved follow-up of true outcomes in patients who transfer-out and better recording practices related to HIV care and treatment especially for ART.